Single Stage Microinverter Based on Two-Switch DC-DC Flyback Converter - Bielskis, Edvardas; Baskys, Algirdas; Sapurov, Martynas (Elektronika ir Elektrotechnika, 2017)
The single stage photovoltaic microinverter based on couple of two-switch DC-DC flyback converters has been suggested. The results of simulation and experimental investigation for the case when photovoltaic microinverter operates in off-grid and grid-tied modes are presented. The proposed single stage microinverter is characterized by simple design and high efficiency.DOI: http://dx.doi.org/10.5755/j01.eie.23.4.18714